Fixed point theorems in partially ordered topological spaces with applications - Taoudi, Mohamed Aziz (Topological Methods in Nonlinear Analysis, 2023)
In this paper, we establish several new fixed point results in the frameworkof topological spaces endowed with a partial order. Special attention is paid to the case that the topology is induced by a metric.Our conclusions generalize many well-known results. Several examplesand illustrative applications are provided to support the exposed results.